SISTEM PAKAR PENYELEKSIAN KULIT ULAR UNTUK EKSPOR MENGGUNAKAN METODE FORWARD CHAINING PADA CV. ALONA JAYA - Asri Mauliani; Andronias Siregar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
Snake skin is one type of reptile skin that has now been used as a commodity trade with a fairly high price. Snake skin that is ripe for export certainly experienced some process first, one of the process is the selection to know the skin into the category class I, II or III. CV. Alona Jaya is a company engaged in the export of reptile skin. Human resources owned CV. Alona Jaya not all experts in the field of skin selection, so still need the help of experts in handling the process. Expert system applications capable of imitating the work of an expert in various fields, one of them is snake skin selection. This expert system is built using forward chaining method, as a search technique that starts from a known fact to reach a goal. The design of this application using UML and Visual Basic programming language with Microsoft Access database as its application. This research produces an expert system application that can be used in snake skin selection for export, so it can help human resources who are not experts at the time of skin selection